A case of bortezomib-associated thrombotic microangiopathy in a multiple myeloma patient. Issue 1 (February 2020) - Moreira Fonseca, Nuno; Cardoso, Filipa; Monteiro, Manuel; Góis, Mário; Sousa, Helena; Fidalgo, Teresa; Calado, Joaquim; Nolasco, Fernando
Bortezomib is a first-generation proteasome inhibitor used in the treatment of multiple myeloma. We present a case of a 70-year-old woman with multiple myeloma, who presented thrombotic microangiopathy with multi-organ involvement thrombotic microangiopathy (ocular, cardiac, and renal) after bortezomib initiation. A kidney biopsy confirmed the diagnosis of thrombotic microangiopathy. A temporal relation between bortezomib exposure and thrombotic microangiopathy onset was seen in the absence of other concurrent medication or disease known to cause thrombotic microangiopathy, and thrombotic microangiopathy was only resolved after drug discontinuation. The exact pathophysiological mechanism remains unknown. To our knowledge, this is the second biopsy-proven published case of bortezomib-associated thrombotic microangiopathy. Since bortezomib is extensively used for treating patients with multiple myeloma, prescribing clinicians should maintain a high index of suspicion of this potentially fatal complication.